The Social Messages in The Ramayana: Perspektif on Literary Theory - Mirza Fathimajauhar Kamalia; Wildayati Wildayati; Artha Fernando; Iskamar Iskamar; Ismi Imroatus Saada (SULUK: Jurnal Bahasa, Sastra, dan Budaya, 2020)
The story of Ramayana has been deeply rooted in the community and is a material for literary studies that has never completed for discussion. In Java the epic, Ramayana first fully appeared in the form of a relief at the Lara Jonggrang Temple which was built around the year 782 to 872.The other emergence about the Ramayana story was in the composition which was in the form ofRamayana kakawin in Old Javanese. The Ramayana story begins with a blessing and a preface including a summary of the story which then contains verses of poetry. This study aims to convey the social messages contained in the Ramayana story to the public. This study uses qualitative research method based on the study of literature in the book of P. Lal (1981) which has been translated into Indonesian. The results of this study are (1) Explaining the social messages contained in the Ramayana story, (2) Explaining the exemplary wisdom of the character Rama, (3) Explaining the exemplary loyalty of the character Sita, (4) Explaining the example of Rahwana's character in the form of perseverance and sincerity in loving Sit, (5) Explaining ibrah (lessons) from the Ramayana story so that it can be used as the life learning. Overall, it can be understood that in the Ramayana there are many social messages that can be used as the exemplary life.